How to Know a Person : The Art of Seeing Others Deeply and Being Deeply Seen - Brooks, David, 1961- (New York : Random House, 2023)
Drawing from the fields of psychology and neuroscience and from the worlds of theater, philosophy, history and education, one of the nation's leading writers and commentators helps us become more understanding and considerate toward others, and to find the joy that comes from being seen.
Part 1: I see you. The power of being seen -- How not to see a person -- Illumination -- Accompaniment -- What is a person? -- Good talks -- The right questions -- Part 2: I see you in your struggles. The epidemic of blindness -- Hard conversations -- How do you serve a friend who is in despair? -- The art of empathy -- How were you shaped by your sufferings? -- Part 3: I see you with your strengths. Personality : what energy do you bring into the room? -- Life tasks -- Life stories -- How do your ancestors show up in your life? -- What is wisdom?
Includes bibliographical references (pages 277-291) and index.
Keywords: Social interaction; Social psychology; Caring; Interpersonal relations; PHILOSOPHY / Ethics & Moral Philosophy; Social interaction